2001
DOI: 10.2139/ssrn.289546
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Capital Structure

Abstract: This essay is a contribution to the empirical literature on the effect of inflation tax on capital structure. A simple empirical model considering the main results of the current theoretical development is studied, using microdata from a number of American corporations. Abstrakt Tento článek je příspěvkem k empirické literatuře studující dopad inflace na strukturu kapitálu. Jednoduchý empirický model používající mikroekonomická data o amerických korporacích je analyzován s ohledem na hlavní poznatky současné t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Similar statement also found on several previous studies e.g. Barry et al, [22], Noguera [23], and Koksal and Orman [24].…”
Section: F Inflationsupporting
confidence: 92%
“…Similar statement also found on several previous studies e.g. Barry et al, [22], Noguera [23], and Koksal and Orman [24].…”
Section: F Inflationsupporting
confidence: 92%
“…Hortlund (2005: 23) proved that a high inflation rate increases the debt ratio, especially for banks. The positive effect of the inflation rate on leverage is also concluded by Frank and Goyal (2009), Mokhova andZinecker (2014), andNoguera (2001). These studies revealed that high inflation creates a high demand for corporate bonds.…”
Section: Inflation Ratementioning
confidence: 69%